-m-3m=16

Simple and best practice solution for -m-3m=16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -m-3m=16 equation:


Simplifying
-1m + -3m = 16

Combine like terms: -1m + -3m = -4m
-4m = 16

Solving
-4m = 16

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '-4'.
m = -4

Simplifying
m = -4

See similar equations:

| (3x-11)/8=x | | 72=(x-1)(x)(x+9) | | 7X+5.5Y=119 | | sqrt-7x+5=sqrt-3x+9 | | 3n-6n=-15 | | 4y-13= | | 4y+38=20+8y | | 2(x+15)=x+21 | | y(49/60)=(7/2) | | x+15=x+21 | | =ln(0.5x^2) | | ((x^2)+y)dx=-xdy | | 6(2n-2)=(8n+8)+1 | | a=1/2bc2 | | (5x-14)+90+y=180 | | 3n-1=-28 | | 4a+8=2a | | 5m-1=14 | | 5L-12=38 | | (2x+13)+3x+57=180 | | -k+5=24 | | -8j-59=13 | | 5*x+57= | | 14i-5=-33 | | 14I-5=-93 | | 3(x-2)+2x=7-(x+5) | | (2c-3)(2c+4)(2c-1)=0 | | 70=(x*x+2*2) | | -12g-4=44 | | -10m+8=-8 | | (x^2+9x+4)=0 | | 6(x-5)=50-4x |

Equations solver categories